Is the Presence of the Father of the Baby during First Prenatal Ultrasound Study Visit Associated with Improved Pregnancy Outcomes in Adolescents and Young Adults? - Sara H. Lee; Rina Lazebnik; Margaret Kuper-Sassé; Noam Lazebnik (International Journal of Pediatrics)
This study examined whether the presence of the father of the baby (FOB) at the first prenatal ultrasound study (US) visit of pregnant adolescents and young adults (AYA) is a marker for improved pregnancy outcomes. Charts of 400 pregnant AYA aged 14–22 years seen at an academic maternity hospital were assessed retrospectively for support persons brought to prenatal US visits. Logistic regression analysis was used to examine the association between FOB presence and gestational age and birth weight. Of 400 charts with support person recorded, 298 charts with first US visit data, singleton birth, and complete gestational data available were analyzed. FOB was present at 30.2% of visits, while the parent of the mother was present at 34.2% of visits. With FOB present, 3.3% of infants were born preterm (gestational age < 37 weeks) compared with 10.5% of infants with FOB absent (p=0.04). Patients with FOB present also had significantly earlier gestational age at the first US visit (15 weeks) than those who did not (19 weeks; p=0.02). For AYA, the presence of FOB at initial prenatal US visits is a predictor of improved pregnancy outcome and likely represents increased support during the pregnancy.